Synthesis, column packing and liquid chromatography of molecularly imprinted polymers for the acid black 1, acid black 210, and acid Brown 703 dyes. Issue 30 (6th July 2022) - Ali, Faiz; Shah, Zuber; Khan, Alamgir; Saadia, Maria; AlOthman, Zeid A.; Cheong, Won Jo
Abstract : MIP synthesis for the recently emerging dyes, a new method for their characterization in liquid chromatography by packing packing the MIP particles in a stainless steel column, and their application in environmental remediation. Abstract : Molecularly imprinted polymers have been synthesized for the acid black 1, acid black 210, and acid brown 703 dyes using methacrylic acid, ethylene glycol, and azobisisobutyronitrile as the monomer, cross-linker, and initiator, respectively, in the ratio of 1 : 10 : 44 (template:monomer:cross-linker). The MIPs were used for the selective removal of their corresponding dyes. The selective nature of the MIPs towards their respective dyes was confirmed by a homemade liquid chromatography system. The resultant polymer materials were packed in a stainless steel column and checked for the separation of mixtures of dyes in liquid chromatography. The dyes complementary in structure to the imprinted cavities in the MIPs had long retention times, showing the highly selective nature of the MIPs. The pH, quantity of the MIPs, time, and concentration of the dyes were optimized for the highly efficient removal of the newly synthesized MIP adsorbents in batch adsorption studies. First-order, second-order, and intra-particle diffusion models were applied to all the three MIP-based adsorbents for their kinetic investigations towards the dyes. All the three MIPs selectively absorbed their target template molecule in the presence of four other template dyes having closely related structures with % RSD < 4% for the three batch experiments. The synthesized MIPs were characterized by FTIR, SEM imaging and liquid chromatography. FTIR results strongly confirmed the presence of hydrogen bonding interactions (600–900) between the template and the individual monomers present in the unwashed MIPs. Liquid chromatography revealed the highly selective nature of the MIPs towards their template molecules. The synthesized polymeric substances possess excellent thermal, chemical, and mechanical stability and can be reused several hundred times. The MIPs were applied in the removal of dyes from spiked water samples (river water, tap water and distilled water) where the % removal of the dyes by their corresponding MIPs was greater than 90%.